Exceptional superelasticity via heterogeneity-driven texture optimization in equiaxed CuAlMn alloys - Xinghao Li; Ye Cui; Guangda Zhao; Lixin Sun; Yang Zhang; Zhongwu Zhang (Materials Futures)
Achieving high superelasticity in polycrystalline shape memory alloys is fundamentally limited by strain incompatibilities arising from grain orientation. Realizing high martensitic transformation strain ( ${ε _{{\text{TS}}}}$ ) orientations that are favorable for superelasticity in equiaxed microstructures remains a major challenge. Here, a novel heterogeneity-driven texture optimization strategy is reported to enhance superelasticity in CuAlMn alloys through controlling high- ${ε _{{\text{TS}}}}$ orientations. Controlled deformation imprints dislocation density heterogeneity in differently oriented grains, leading to the gradients of sub-boundary energy. These gradients drive selective grain boundary migration, facilitating the preferential growth of grains with the high- ${ε _{{\text{TS}}}}$ <015> orientation. As a result, the fraction of <015>-oriented grains increases significantly from ∼19% to ∼70%, yielding a unprecedent tensile superelastic strain of ∼8.0% in equiaxed CuAlMn alloys, paving the way for practical engineering applications. This microstructural heterogeneity-guided strategy offers a general framework for overcoming texture-related limitations in polycrystalline functional materials.